PERBANDINGAN SUHU RUANG ANTARA PENGGUNAAN DINDING BATA DAN DINDING KAYU - Malik Abdul Aziz; Rahmat, Syahril (Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Padang, 2025)
This study aims to compare indoor air temperature between brick wall and wooden wall buildings and to evaluate their thermal comfort based on national standards. A quantitative approach with field experimental methods was employed. Temperature measurements were conducted in two rooms with similar geometry and orientation but different wall materials. Temperature data were recorded hourly for 24 hours over three consecutive days. Data analysis was carried out descriptively by comparing average temperatures and daily temperature fluctuations based on SNI T-14-1993-037. The results indicate that rooms with brick walls exhibit more stable indoor temperatures with smaller daily fluctuations, while rooms with wooden walls tend to be cooler at night but experience higher temperature increases during the daytime. Overall, both wall types fall within the thermal comfort range, although they demonstrate different thermal performance characteristics.